Gottfried Wilhelm Leibniz - Dascal, Marcelo. author. aut Link
LXXII, 520 p.
Keywords: Leibniz is known to the wide public and to many scholars mainly as a logician and mathematician, and as the creator of a fascinating but strange metaphysical system. In these, as well as in other fields, his remarkable innovations were achieved through painstaking efforts to establish a fruitful critical dialogue with the leading contemporary thinkers. He was no less important, however, in his practical endeavor to bring opponents to negotiate reasonable solutions to key political and religious conflicts of his time. Both his theoretical and practical activities were informed by a philosophical mind that sought in all circumstances the most general underlying principles; by a juridical mind that sought to bring order and structure to human interaction, without sacrificing the necessary flexibility; by an argumentative mind that knows that persuading is often more important than proving; by a scientific mind eager to organize past and present knowledge so as not to miss any bit of information capable of pointing the way to new discoveries; by a theologian mind that refuses to admit that religious conflicts between true believers are irresolvable; and by an ethical and political mind whose major concern is to direct all our intellectual work towards improving the well-being of humankind. All these perspectives (and more) are united in what this book identifies as his Art of Controversies, which might also be called an Art of Dialectical Cooperation. For it is based on the idea that knowledge production, acquisition, and evolution is not a one-man affair, but the result of the cooperation of many, coming from different perspectives; whence it follows that not only tolerance vis-à-vis the other, but also valuing the other’s contribution and integrating it – whether it stems from another age, continent, culture, discipline, religion, or individual – is indispensable. This dialectical Leibniz that emerges from the selected texts heretranslated, commented, and interpreted in the light of their context, isn’t for sure the familiar one. Yet, perhaps surprisingly, it is capable of shedding light on that old, familiar, yet incomplete image of Leibniz, and of adding thus a further reason for cherishing and cultivating the heritage of a truly great man.